2017
DOI: 10.1177/1059601116688612
|View full text |Cite
|
Sign up to set email alerts
|

How Does a Reward for Creativity Program Benefit or Frustrate Employee Creative Performance? The Perspective of Transactional Model of Stress and Coping

Abstract: We explore the effect of a reward for creativity program on employee creativity in organizations by investigating the underlying mechanisms based on the transactional model of stress and coping-a novel theoretical perspective for this research area. We theorize and find in two field studies that challenge appraisal of a reward for creativity program (perceived potential for gain, growth, or mastery) is positively related to problemfocused coping, which in turn predicts high creative performance. By contrast, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 90 publications
(137 reference statements)
0
33
0
1
Order By: Relevance
“…The regression result for model 1 (see Table 5) has implicated that value-reward leadership practice significantly relates to productivity of the university's academic and non-academic staffs. Building on that premise it stands to affirm how enforcing integrative and coherent reward system, revolving around equity, justice, and fair play is critical to unleashing staff's creative and innovative thinking on one hand (Li, Chen, & Lai, 2017;Al Darmaki, Omar, & Wan Ismail, 2019) and the integrity and oneness of the group on the other hand (Fudge & Schlacter, 1999).…”
Section: Discussion Value Reward Leadership and Staff Productivitymentioning
confidence: 99%
“…The regression result for model 1 (see Table 5) has implicated that value-reward leadership practice significantly relates to productivity of the university's academic and non-academic staffs. Building on that premise it stands to affirm how enforcing integrative and coherent reward system, revolving around equity, justice, and fair play is critical to unleashing staff's creative and innovative thinking on one hand (Li, Chen, & Lai, 2017;Al Darmaki, Omar, & Wan Ismail, 2019) and the integrity and oneness of the group on the other hand (Fudge & Schlacter, 1999).…”
Section: Discussion Value Reward Leadership and Staff Productivitymentioning
confidence: 99%
“…Although research has primarily focused on the impact of stress appraisal for strainrelated outcomes, the original theory proposed that stress appraisals could have broad implications for a range of outcomes in the context of an unfolding stressful situation, including motivational and social consequences (Lazarus & Folkman, 1984). Indeed, scholars have found that challenge appraisal of workplace stressors is negatively associated with workplace procrastination (Prem et al, 2018), whereas hindrance appraisal is associated with more procrastination (Prem et al, 2018) and less creative performance (Espedido & Searle, 2018;Li, Chen, & Lai, 2018). Moreover, there is research that demonstrates challenge job stressors (e.g., workload, responsibility, complexity) are positively associated with citizenship behaviors, whereas hindrance job stressors (e.g., role ambiguity, conflict, hassles) are negatively associated with citizenship behaviors (Rodell & Judge, 2009;Kim & Beehr, 2018; see also Webster et al, 2010), and that these associations can be both direct and indirect STRESS APPRAISALS OF PERFORMANCE PAY 9 through affective and motivational processes.…”
Section: Stress Appraisals Of Performance Paymentioning
confidence: 99%
“…In a related vein, Searle and Auton (2015) found that workers appraised time pressure as a challenge to the same degree as a hindrance. In summary, several empirical studies support the merits of including appraisals of job demands in work psychological research by demonstrating that these appraisals consistently explain unique variance in a study’s outcome variables (e.g., creative performance, Li et al, 2018 ; affect, Searle and Auton, 2015 ). Thus, it is imperative to extend current research to consider the role of appraisals on the effects of job characteristics.…”
Section: Introductionmentioning
confidence: 91%